2008
DOI: 10.1007/s11292-008-9053-5
|View full text |Cite
|
Sign up to set email alerts
|

How you can tell if the simulations in computational criminology are any good

Abstract: Computational criminology applies computer simulations to study topics of interest for criminologists. Just as for all computer modelling in science, the validity of the simulations ultimately depends on whether they are able to reproduce empirical phenomena with sufficient accuracy. The only way in which this can be determined is by comparing model output to real observations. This paper provides an overview of how such model evaluations can be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 53 publications
(43 reference statements)
0
35
0
3
Order By: Relevance
“…There are several questions regarding the validity of the simulated model and its implications for criminological theories. Three criteria for 'validating' computer models have been proposed [38]. The qualitative credibility is established if the model is consistent with what is expected of the result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several questions regarding the validity of the simulated model and its implications for criminological theories. Three criteria for 'validating' computer models have been proposed [38]. The qualitative credibility is established if the model is consistent with what is expected of the result.…”
Section: Discussionmentioning
confidence: 99%
“…The internal quantitative credibility is met when the model output corresponds to observations that are a part of the data used to develop and calibrate the model. Furthermore, external quantitative credibility corresponds to the situation when the model output corresponds well to observations from data not used to develop and calibrate the model [38]. It needs to be kept in mind that in social sciences good and even valid evaluation data is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly specified models can be validated by comparing model output to aggregate statistics, and individual agent behavior to observed behaviors in a comparable population (Bruch and Atwell 2013; for a summary of empirical validation approaches, see Berk 2008). On the other hand, abstract models can be compared to observed patterns (Grimm et al 2005) or to hypothesized empirical relationships, which are based on observed mechanisms (Bruch and Atwell 2013).…”
Section: Simulation Challenges and Opportunitiesmentioning
confidence: 99%
“…Berk (2008) examines the complexities of model validation, specifically degrees of credibility, for computational models and further concludes that simulation models can benefit the development and refinement of theory. However, criminologists must continue to test computer models against data [13]. Further, Townsley and Birks (2008) discuss the need for replication of computational model to enhance their validity [14].…”
Section: Introductionmentioning
confidence: 99%